1982
DOI: 10.1113/jphysiol.1982.sp014083
|View full text |Cite
|
Sign up to set email alerts
|

Inputs to testosterone‐sensitive stria terminalis neurones in the rat brain and the effects of castration.

Abstract: SUMMARY1. The inputs to cortico-medial amygdala neurones which project directly to the area of the medial preoptic/anterior hypothalamic junction were studied electrophysiologically in urethane anaesthetized male rats.2. In experiments with fifteen male rats it was found that none of these neurones was responsive to electrical stimulation of the ipsilateral olfactory bulb or accessory olfactory bulb or odour stimulation.3. Experiments with four rats showed that electrical stimulation of the lateral portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There was no significant difference between the two groups for the number of orthodromically stimulated neurones encountered during each electrode penetration In the previous paper (Kendrick, 1982) it was concluded that there was a fimbria input to the cortico-medial amygdala (c.m.a.) probably via the basolateral nucleus of the amygdala (b.l.n.).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…There was no significant difference between the two groups for the number of orthodromically stimulated neurones encountered during each electrode penetration In the previous paper (Kendrick, 1982) it was concluded that there was a fimbria input to the cortico-medial amygdala (c.m.a.) probably via the basolateral nucleus of the amygdala (b.l.n.).…”
Section: Resultsmentioning
confidence: 98%
“…to the m.p.o.a.h., via, presumably, the corticohypothalamic tract (Raisman, Cowan & Powell, 1966). This direct projection via the corticohypothalamic tract is, however, ipsilateral (Raisman et al 1966) whereas the present projection via the amygdala is contralateral in origin (Kendrick, 1982). Hubbard et al (1981) reported that for more anterior locations the most effective part of the i.f.i.m.b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations